SEL PLASMA LEUKEMIA HUBUNGAN DENGAN MIELOFIBROSIS - Sri Sulistiandari; Budiman . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Plasma cell leukemia (PCL) is a variant form of myeloma which contain more than >20% plasma cells and an absolute plasmacell content ≥ 2.000/mm3 in peripheral blood. PCL is a rare disorder, whole PCL with myelofibrosis is even more rare disorder. Thecorrelation between plasma cell leukemia and myelofibrosis is unclear. A 59-years-old woman referred to our hospital with generalweakness and severe anemia. Physical examination: looks pale, anaemic of conjunctiva, hepatosplenomegaly. The laboratory findingsare Hb 4.1 gr/dL, MCV 81 fL, MCH 26.7 pg, leucocytes 22.500/mm3, thrombocytes 26.000/mm3, reticulocytes 1.8%. The peripheralblood showed leucoerythroblastic morphology with teardrop cells and 32% plasma cells. Bone marrow aspiration revealed massiveplasma cell infiltrations (90%). Protein electrophoresis showed hypogammaglobulinemia. There is no evidence of osteolitic bone lesionon radiological examination. Clinical and laboratory finding above support the diagnosis of Primary Plasma Cell Leukaemia that maylead to myelofibrosis as a complication. Bone marrow biopsy is required to confirm diagnosis of myelofibrosis.